Three-dimensional Corporate Social Responsibility Model of a Postal Service Provider - Unterberger, Marija; Vešović, Predrag; Mostarac, Katarina; Šarac, Dragana; Ožegović, Spasenija (Promet - Traffic&Transportation, 2018)
In this paper, the term “corporate social responsibility” (CSR) was first observed based on the existing pyramid, which defines CSR as a set of economic, legal, ethical, and philanthropic activities. Then the dimensioning of the model of corporate responsibility in postal system was performed, where seven categories of the CSR model were defined. Only one category (out of seven) represents a set of all four activities defined by the existing pyramid. Based on this, a new model of CSR in the postal system was developed, that is seen through the development of three dimensions of the postal network: physical (PH), electronic (E), and financial (F). The main objective of the paper is to define a CSR model that will ensure the economic, social, and environmental development of the postal market by synergistic operation of all three dimensions of the postal network. An analysis of the existing state of the postal services market was carried out, and then the level of the future development of the postal network was determined. Through evaluation or systematic and objective assessment of the CSR model based on the determined parameters, measurability of the CSR model is assured. This paper deals with the case of the public postal operator (PPO) in the Republic of Serbia (RS).